2010
DOI: 10.1111/j.1600-0889.2010.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of terrestrial ecosystems in determining CO<sub>2</sub> stabilization and recovery behaviour

Abstract: Terrestrial ecosystems are sensitive to climate and can also influence it through both biophysical and biogeochemical feedbacks. Natural carbon uptake by ecosystems will control future evolution of CO2 and climate, but the ecosystems themselves may be committed to long‐term changes. Here we use a coupled climate‐carbon cycle GCM with dynamic vegetation to investigate the policy‐relevance of these feedbacks in several idealized scenarios. Our results show that the natural carbon cycle in the ocean and on land c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…11). In agreement with Jones et al (2010), a larger boreal forest extension in the DYN simulation than in the STAT simulation leads to an additional terrestrial carbon storage in the northern high latitudes. In comparison to the STAT simulation, the carbon storage is higher in the south and lower in the north of South America, as the tropical trees shift southward in the DYN simulation.…”
Section: Biogeochemical Effect Of Vegetation Dynamics On Climatesupporting
confidence: 68%
See 1 more Smart Citation
“…11). In agreement with Jones et al (2010), a larger boreal forest extension in the DYN simulation than in the STAT simulation leads to an additional terrestrial carbon storage in the northern high latitudes. In comparison to the STAT simulation, the carbon storage is higher in the south and lower in the north of South America, as the tropical trees shift southward in the DYN simulation.…”
Section: Biogeochemical Effect Of Vegetation Dynamics On Climatesupporting
confidence: 68%
“…Based on simulations made with Global Dynamic Vegetation Model coupled to Atmospheric General Circulation Models, the shifts in vegetation cover due to an increased atmospheric CO 2 concentration and the resulting influence on the climate (Notaro et al, 2007;O'ishi and Abe-Ouchi, 2009;Yurova and Volodin, 2011) and on the carbon cycle (Jones et al, 2010) Notaro et al (2007) assume four times pre-industrial atmospheric CO 2 concentrations and find that increased temperatures in the northern high latitudes lead to a northward expansion of boreal forests. The extended tree cover leads to further warming since the surface albedo is reduced.…”
Section: U Port Et Al: the Influence Of Vegetation Dynamics On Anthmentioning
confidence: 99%
“…In addition, uncertainty in predicted vegetation change could arise from the uncertainties in our understanding of the mechanisms about climate-induced tree change, particularly regarding the physiological mortality thresholds and interdependencies of the metabolism of carbohydrates, water, and defense Fisher et al 2010;McDowell 2011). The varying results from studies using different DGVMs (e.g., Bergengren et al 2001;Cox et al 2004;Jones et al 2010) highlight the limitations in our understanding of vegetation-climate relationships, and indeed, in understanding vegetation dynamics overall. Vegetation distributions in DGVMs are predicted using simple bioclimatic relationships (temperature and moisture limits) with no barriers to species migration (Higgins and Harte 2006;Alo and Wang 2008).…”
Section: Discussionmentioning
confidence: 91%
“…For example, some studies (e.g., Cox et al 2004;Jones et al 2010) found that vegetation carbon was projected to increase in the forested regions of the Northern Hemisphere mostly as a result of CO 2 -fertilization of photosynthesis under ''business as usual'' or other idealized emission reduction scenarios. Warming could also lead to a longer snow-free period and therefore extend the growing season in the boreal regions (e.g., Harris et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…It is now established not only that human activities have been the primary cause of observed global warming (IPCC 2007), but also that the climate system is already committed to further global warming arising from physical (e.g., (Meehl et al 2005)), biogeochemical (e.g., (Jones et al 2010)), socio-political (e.g., (Matthews and Weaver 2010)) and infrastructural (e.g., (Davis et al 2010)) inertia. In addition, continued unconstrained increases in greenhouse gas emissions are likely to cause global warming that substantially exceeds the internationally agreed-upon target (UNFCCC 2009) of 2 °C above the pre-industrial baseline (e.g., (Matthews et al 2009; Meinshausen et al 2009)).…”
Section: Introductionmentioning
confidence: 99%